2012
DOI: 10.1371/journal.pone.0039701
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of Thalamic Nuclei in Idiopathic Generalized Epilepsy Revealed by a Study Combining Morphological and Functional Connectivity MRI

Abstract: ObjectiveNeuroimaging evidence suggested that the thalamic nuclei may play different roles in the progress of idiopathic generalized epilepsy (IGE). This study aimed to demonstrate the alterations in morphometry and functional connectivity in the thalamic nuclei in IGE.MethodsFifty-two patients with IGE characterized by generalized tonic-clonic seizures and 67 healthy controls were involved in the study. The three-dimensional high-resolution T1-weighted MRI data were acquired for voxel-based morphometry (VBM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
67
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 43 publications
(46 reference statements)
13
67
1
4
Order By: Relevance
“…4 Wang et al 8 identified abnormal thalamic nuclei in a group of patients with IGE by morphologic analysis, which provided the foundation for seed-based functional connectivity analysis. This revealed decreased connectivity between the medial dorsal nucleus and bilateral orbital frontal cortices, caudate nucleus, putamen, and amygdala.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Wang et al 8 identified abnormal thalamic nuclei in a group of patients with IGE by morphologic analysis, which provided the foundation for seed-based functional connectivity analysis. This revealed decreased connectivity between the medial dorsal nucleus and bilateral orbital frontal cortices, caudate nucleus, putamen, and amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Hemodynamic changes associated with GSWDs have been consistently observed in the thalamus and default mode areas. 5 Recently, corticothalamic interactions in generalized epilepsy have been characterized by morphometric covariance, 6 functional and anatomic connectivity, 7,8 and causal influence. 9 In particular, corticothalamic connections (parcellated through probabilistic tractography) showed abnormal functional connectivity in juvenile myoclonic epilepsy.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed disrupted SN in relation to inter-ictal spikes in children with focal (temporal and extra-temporal) intractable epilepsy (Ibrahim et al, 2014). In addition, it has been observed that thalamic deactivation is associated with inter-ictal discharges in generalised epilepsy (Wang et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the first aim of the current study focused on evaluating subsampling protocols for manual estimation of ICV in the following four different subject categories: control pediatrics, control adults, pediatrics with epilepsy and adults with Alzheimer's disease. The choice of these groups were based on the importance of the ICV measure as a critical normalization factor whether the study is based on AD (Jack, Knopman et al 2012;Jack Jr, Knopman et al 2013;Westman, Aguilar et al 2013;Zhou, Goryawala et al 2014) or on epilepsy (Whitwell, Crum et al 2001;Wang, Zhang et al 2012;Winston, Cardoso et al 2013;Germeyan, Kalikhman et al 2014). …”
Section: Intracranial Volume Estimationmentioning
confidence: 99%